Moving the museum Indigenous + Canadian art at the AGO - Nanibush, Wanda 1976-; Uhlyarik, Georgiana ca. 20. Jh (Goose Lane Editions, 2023)
Moving the Museum documents the reopening of the J.S. McLean Centre for Indigenous & Canadian Art with a renewed focus on the AGO’s Indigenous art collection. The volume reflects the nation-to-nation treaty relationship that is the foundation of Canada, asking questions, discovering truths, and leading conversations that address the weight of history and colonialism. Lavishly illustrated with more than 100 reproductions, Moving the Museum: Indigenous + Canadian Art at the AGO features the work of First Nations artists - including Carl Beam, Rebecca Belmore, and Kent Monkman - along with work by Inuit artists like Shuvinai Ashoona and Annie Pootoogook. Canadian artists include Lawren Harris, Kazuo Nakamura, Joyce Wieland, and many others. Drawing from stories about our origins and identities, the featured artists and essayists invite readers to engage with issues of land, water, transformation, and sovereignty and to contemplate the historic and future representation of Indigenous and Canadian art in museums
Catalogue of an exhibition held at the Art Gallery of Ontario's J.S. McLean Centre for Indigenous + Canadian Art beginning June 30, 2018
Includes bibliographical references
Keywords: Art Gallery of Ontario; Indigenes Volk; Nationale Minderheit; Kunst; Ausstellung; Minderheit; Kanada; Indigenous art / Canada / Exhibitions; Art, Canadian / Exhibitions; Art autochtone - Canada - Expositions; ART; ART / Canadian; ART / Collections, Catalogs, Exhibitions / Permanent Collections; ART / History / Canadian; ART / Museum Studies; Art, Canadian / (OCoLC)fst00816079; Indigenous art / (OCoLC)fst01741814; exhibition catalogs; Exhibition catalogs / (OCoLC)fst01424028; Exhibition catalogs; Catalogues d'exposition; Canada / (OCoLC)fst01204310; Bildband